The nature of problem solving: using research to inspire 21st century learning - Csapó, Benő; Funke, Joachim (Educational Research and Innovation, 2017)
Solving non-routine problems is a key competence in a world full of changes, uncertainty and surprise where we strive to achieve so many ambitious goals. But the world is also full of solutions because of the extraordinary competences of humans who search for and find them. We must explore the world around us in a thoughtful way, acquire knowledge about unknown situations efficiently, and apply new and existing knowledge creatively. The Nature of Problem Solving presents the background and the main ideas behind the development of the PISA 2012 assessment of problem solving, as well as results from research collaborations that originated within the group of experts who guided the development of this assessment. It illustrates the past, present and future of problem-solving research and how this research is helping educators prepare students to navigate an increasingly uncertain, volatile and ambiguous world.